Penerapan Teknologi Force Molting pada Ayam Petelur Afkir: Kajian Parameter Produksi, Organ Pencernaan dan Reproduksi, Pertahanan Tubuh - Mulyono, Ali Mursyid Wahyu; Sariri, Ahimsa Kandi; Husodo, Wisnu Tri (Universitas Sebelas Maret (UNS), 2008)
The research was aimed to study the egg production, digestion and reproduction tract, and body protection parameters of the force molting (FM) technology application on rejected laying hen. Thirty-six rejected laying hens were randomly devided into two kinds of treatment (T0 and T1), with three replication each. Each replication consisted of six hens. T0 (control) was ad libitum feeding during the research. T1 was FM treatment of six-days feed fasting, continued by restricted feeding (corn 50 g/hen/day) for 29 days. After the treatment, T1 was fed as T0 for 3 x 28 days period. Water was given ad libitum for T0 and T1. Variables observed included production and egg quality, length and weight of the parts of digestion and reproduction tract, and blood profile. The result of the research showed that FM treatment on rejected laying hens significantly increased the percentage of egg production and egg-mass, decreasing feed conversion ratio, but it insignificantly influenced on feed consumption and egg quality. The weight and length of the parts of digestion and reproduction tract were insignificantly influenced by FM treatment, except of gizzard, magnum and uterus weight, and isthmus length. The FM treatment was insignificantly influenced the body protection parameters. It was concluded that the force molting technology on rejected laying hen could re-activation of egg production without effecting on the parts of digestion and reproduction organ, and body protection parameters. Key words: Force molting, rejected laying hen, egg production, digestion and reproduction tract, body protection